The Influence of Disney Musical Practice Course on the Mental Health of Chinese Left-Behind Children from the Perspective of Art Communication - Wei Cao (Occupational Therapy International)
Background. In recent years, with a large number of rural people going out to work, the mental problems of left-behind children have been widely concerned by people from all walks of life. Objective. The purpose is to improve the teaching quality of music education of left-behind children and solve their unique mental problems. Methods. Based on the questionnaire survey, the mental state of left-behind children is studied, and the mental problems of left-behind children are intervened based on musical practice classes. First, the left-behind children’s mental status is studied. Second, through the questionnaire, the left-behind children’s music classroom status is studied and analyzed. Then, the musical classroom intervention experiment is designed to prevent and adjust the left-behind children’s mental problems. Results. The results show that more than 90% of left-behind children spend less than one month with their parents every year. Most of the left-behind children are supervised by their grandparents, and 68% of them have been accompanied by their grandparents for more than nine months. Due to the lack of parents’ company, most of the left-behind children are lack of self-confidence and timid and tend to care about others’ opinions. Musical practice classes have a good effect on the regulation and prevention of left-behind children’s mental problems. Conclusions. This study uses a questionnaire survey method to explore the new form of left-behind children’s music classroom, preventing and regulating left-behind children’s mental problems, which provides a reference for the research in related fields.